2019
DOI: 10.5617/adno.6473
|View full text |Cite
|
Sign up to set email alerts
|

“The Sustainable Backpack”: Exploring possibilities in education for sustainable development through a nationwide professional development program

Abstract: Education for sustainable development (ESD) provides crucial opportunities for young people to be involved authentically in addressing socio-ecological challenges in their local and global communities. While many studies on education for sustainable development have documented efforts within higher education, few examples exist of large-scale programmes that engage primary and secondary students. Norway’s Sustainable Backpack programme is a notable exception. In this paper, we present insights from this nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
0
7
0
3
Order By: Relevance
“…In collaboration with teacher teams, we have directed attention to the unused potential of different subjects in terms of exploration, argumentation, critical thinking and ethical issues. To encourage a more pluralistic approach to teaching, we have introduced wicked problems, placing emphasis on students' argumentation and critical skills (Scheie & Stromholt, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In collaboration with teacher teams, we have directed attention to the unused potential of different subjects in terms of exploration, argumentation, critical thinking and ethical issues. To encourage a more pluralistic approach to teaching, we have introduced wicked problems, placing emphasis on students' argumentation and critical skills (Scheie & Stromholt, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In response to the Decade of Education for Sustainable Development and the Norwegian strategic plan for ESD for the period of 2006-2010 (Utdanningsdirektoratet, 2006), the Sustainable Backpack program (SBP) was initiated by the Ministry of Education and Research and the Ministry of Climate and Environment (Figure 1). Targeting Norwegian primary, secondary and upper secondary schools, the SBP's aim is to increase SD-related awareness, understanding and competencies among teachers and students (Scheie & Stromholt, 2019). Through the SBP, schools can apply for financial and professional teacher training support to develop and implement SD curriculum units in the classroom.…”
Section: The Sustainable Backpack Programmentioning
confidence: 99%
See 1 more Smart Citation
“…He calls for a science curriculum that engages students in developing critical understandings about NOS and prepares future citizens to make informed decisions on socio-scientific issues in democratic societies. Also, Scheie and Stromholt (2019) reported that students (from both primary and secondary schools) involved in authentically socio-ecological challenges in their local communities increased their argumentation skills and raised their faith in own abilities to influence the environment for sustainability.…”
Section: Research On Critical Thinking In Educationmentioning
confidence: 99%
“…Nettverkene i Den naturlige skolesekken (DNS) og i EU-prosjektet SEAS gir laerere kompetanse i å undervise og designe tverrfaglig undervisning innen baerekraftig utvikling. Forskning og utvikling i DNS viser at etablering av undervisning knyttet til utdanning for baerekraftig utvikling tar tid, men skolene har større sannsynlighet for å lykkes ved å etablere kollegial forankring ved skolen, bruke naermiljøet som laeringsarena og samarbeide med eksterne aktører for å motivere både laerere og elever i dette arbeidet (Scheie & Stromholt, 2019). Videre viser forskning på skoleprosjekter i DNS at laerere trenger kompetanse i og støtte til å samarbeide på tvers av fag og bevissthet om at undervisningen bør vaere eksplisitt for at elever skal få en holistisk forståelse av baerekraftig utvikling (Korsager & Scheie, 2019).…”
Section: Utfordringer Og Muligheterunclassified